Teacher job satisfaction and learner performance in South Africa - Iwu, Chux Gervase; ., Henrie Olumide Benedict; ., Robertson Khan Tengeh (Journal of Economics and Behavioral Studies, 2013)
Against the backdrop of the dismal performance of a number of South African high Schools in recent years, this study investigates the relationship between poor performance of learners and teacher motivation in selected high schools in the Western Cape Province of South Africa. Adopting an exploratory approach, a random sample of 279 educators was drawn from the database of the poorly performing high schools as provided by the Western Cape Department of Education. Using closed and open-ended questions, a survey questionnaire was utilized to collect data. The Statistical Package for the Social Sciences (SPSS version 21) was utilised to analyse the data. A number of descriptive statistical tests including Chi Square, and Spearman’s correlation were conducted on the data. The results suggest that highly motivated educators experience job satisfaction; and also perform better than their poorly motivated counterparts. In terms of motivation, the results further suggest that a mix of intrinsic and extrinsic factors tend to exert influence on the educators motivation. For instance, working conditions, job security, and perceived growth opportunities in order of importance were noted to be contributing factors. As far as the obstacles that these educators encounter, lack of resources, work over load and lack of recognition were noted in order of severity. A positive relationship between the factors that influence an educators’ motivation and the level of obstacles encountered was noted. The implication is that, notwithstanding the rankings of the two sets of factors, no factor should be addressed in isolation.